Lactococcus lactis produtor de HSP65 inibe a encefalomielite autoimune experimental murina previnindo a migração de células T para a medula espinhal - Mauro Andrade de Freitas Guimarães (2017)
Multiple sclerosis is a genetic and autoimmune disease that affects the central nervous system. The initial manifestations is an intense immune responses that primainly affect the white matter of the brain and spinal cord, followed by a chronic phase with a neurodegenerative character.Because of the complexity of the disease and the difficulty to treat, has been testing therapeutic alternatives that wold modulate the disease development presenting minimal sides effects. In a previus study, we used a protocol for the induction of oral tolerance using a recombinant HPS65 producing Lactococcus lactis and we obtained good results in the prevention of experimental autoimmune encephalomyelitis (EAE), induced in C57BL / 6 mice by MOG immunization. In the present study, the same protocol was used for the treatment. In the present study, mice received orally HPS65-producing Lactococcus lactis strain for five days after disease induction. The treatment was as efficient in reducing the clinical score of EAE as the prevention protocol. Using histologicalIt analysis and intravital microscopy, we observed that the treatment inhibited the recruitment of leukocytes to the spinal cord, both in the parenchyma and in the blood vessels that irrigate the meninges. In the secondary lymphoid organs, there was an increase in regulatory T cells, especially those that express the membrane form of the cytokine TGF-B in the membrane (LAP). This effect occurred with no alteretion in the frequency of ativadet lynphocytes indicating that there immunoregulation was not associated with immunosuppressive.